The Role of the Spatial Planning and Job Creation Office in the Issuance of Building Permits to Realize Balanced Housing - Lisna Wati Purba; Benny Djaja (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
Home is a basic human need, therefore the state is obliged to guarantee the fulfillment of housing needs by implementing Balanced Housing, this has also been mandated in the 45 Constitution Article 28 H, and strengthened in Law Number 1 of 2011 concerning housing and residential areas. By analyzing statutory regulations associated with legal theories and the constraints faced by the results of the study found that the implementation of balanced residential development with a composition of 1:3:6, namely the construction of 1 (one) luxury housing unit is always accompanied by 3 (three) ) medium housing units and 6 (six) simple housing units are still not implemented properly because of this, so the role of the Government, in this case the Office of Spatial Planning and Job Creation is urgently needed to realize Balanced Shelter.